1978
DOI: 10.1073/pnas.75.10.4967
|View full text |Cite
|
Sign up to set email alerts
|

Lack of correlation between tumorigenicity and level of plasminogen activator in fibroblasts transformed by Rous sarcoma virus

Abstract: We have previously isolated, from agar suspension culture, clones of chicken embryo fibroblasts transformed by B77 and Prague strains of Rous sarcoma virus (RSV) that varied in the expression of plasminogen activator activity [Wolf, B. A. & Goldberg, A. (1976) Proc. Natl. Acad. Sci. USA 73, 3613-3617]. All of the clones exhibited an altered cellular morphology, an increased rate of sugar transport, and a high efficiency of colony formation in agar suspension regardless of the level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1981
1981
1987
1987

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Thus, it is possible that release of this factor may be involved in transformation, either through a plasminogen activator-mediated proteolysis or by a transformation-induced stimulation of endogenous membrane proteases. It must be pointed out, however, that the correlation between plasminogen activator release and transformation is still controversial (Wolf and Goldberg, 1978). In any event, these questions can be answered once the factor has been purified and its receptors identified.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is possible that release of this factor may be involved in transformation, either through a plasminogen activator-mediated proteolysis or by a transformation-induced stimulation of endogenous membrane proteases. It must be pointed out, however, that the correlation between plasminogen activator release and transformation is still controversial (Wolf and Goldberg, 1978). In any event, these questions can be answered once the factor has been purified and its receptors identified.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies investigating the in vitro properties of chemically transformed hamster cells and human osteosarcoma cells show negative correlations between PA production and growth in semisolid agar (2,11). Cell clones selected from Rous sarcoma virus-transformed fibroblasts grown in soft agar show a variability in PA levels, but no difference in tumorigenic potential (22,23). It has also been shown that PA production is not sufficient to cause the absence of large external transformation-sensitive (LETS) protein (15).…”
Section: Discussionmentioning
confidence: 99%
“…While not re quired for the transformed phenotype [4,5], such enzymes have been implicated in the process of invasion and metastasis [1][2][3]6]. In addition to tumor cells, some normal cells such as macrophages and polymorphonu clear leukocytes can contribute proteinases to the extracellular environment when they are stimulated [7,8].…”
Section: Introductionmentioning
confidence: 99%